Crowdsourcing initiatives and the diffusion of information: Experimental evidence from livestock keepers in Kenya - Shikuku, Kelvin Mashisia; Lepariyo, Watson Saewua; Baraza, Meshack; Ochenje, Ibrahim (Elsevier, 2025)
Crowdsourcing initiatives that engage a large group of individuals (the crowd) to perform micro-tasks using information and communication technologies are increasingly utilized for real-time monitoring of shocks and providing advisories to smallholder farmers and livestock keepers. We conducted a randomized control trial (RCT) in northern Kenya to evaluate KAZNET, which is a crowdsourcing initiative for collecting and disseminating near-real-time information about livestock markets, vegetation conditions, and household food security in the drylands of East Africa. The RCT randomly assigned 178 villages to either the treatment arm (exposure to the KAZNET initiative) or the control arm (no KAZNET). We found that the KAZNET initiative improved access to information, increased the adoption of livestock management practices and use of inputs (livestock medicine and insurance), and shaped decisions about the choice of markets for selling livestock. Further, the KAZNET initiative increased livestock income. Together, these findings suggest that efforts and investments to scale agricultural information crowdsourcing initiatives will yield potentially beneficial impacts.